TINJAUAN YURIDIS DALAM BUKTI HUKUM KONSUMEN DALAM MAKANAN HALAL - Jacobus jopie Gilalo; Adi Sulistiyono; Burhanudin Harahap (Magister Hukum Sekolah Pascasarjana Unida, 2020)
Indonesia is a country with the majority Muslims in the world. As Muslims, it is obligatory to comply with religious prohibitions that must be obeyed, namely by not consuming food that are made from / have non-halal contents. Several laws, namely: Consumer Protection Act, Health Act, Food Act and Halal Product Guarantee Act are a form of legal protection for halal food products that can provide guarantees for consumption by Indonesian Muslim communities. This paper is a descriptive qualitative one that seeks to provide an overview of the problem of regulating halal food products in relation to consumer protection and legal protection of consumers in consuming halal food products. The results of this review study that the regulation of halal food products for companies or businesses that will trade their products in Indonesia based on the Halal Product Guarantee Act if related to consumer protection has provided legal certainty for the consumer community (Muslims) to consume halal food, namely by there are Halal Certification marks and Halal Labels. Likewise, several laws and regulations relating to halal food products that have been enacted provide legal protection for consumers in consuming food and beverages. Consumers must get information, safety and a sense of security for a food product that will be consumed according to their choices.